KONTRIBUSI GURU BIMBINGAN DAN KONSELING DALAM MENINGKATKAN KEMANDIRIAN ABK TUNAGRAHITA DI SKH NEGERI 02 KOTA SERANG - Silvia Tri Hastuti; Yahdinil Firda Nadhirah (STKIP Subang, 2026)
This research aims to describe the contribution of Guidance and Counselling teachers in improving the independence of students with intellectual disabilities at SKH Negeri 02 Serang City. The problem addressed is the low level of independence among students with intellectual disabilities, caused by intellectual limitations, suboptimal environmental support, and limited facilities and teaching staff. In this study, the method used is qualitative, with data collection techniques carried out thru participant observation, in-depth interviews, and documentation. The main resource person is a guidance counselor at SKH Negeri 02 in Serang City, with interviews and observations conducted over two days at the school. The research results indicate that guidance counselors play a role as companions, motivators, and connectors between students, classroom teachers, and parents. Guidance counselors utilize modeling and behavioral approaches, and implement self-development programs (daily living) thru the independence laboratory. Independence assessment is conducted thru observation of students' daily activities, such as eating, dressing, and maintaining personal hygiene. The main challenges faced include a limited number of teachers, time constraints, and low public understanding of the needs of students with intellectual disabilities. This research recommends improving facilities, providing regular training for teachers, and educating the public to optimize guidance and counselling services for students with intellectual disabilities.